NURSES AND FIRST FEMALE PHYSICIANS OF THE SERBIAN LITERATURE FROM THE SECOND HALF OF THE 19TH CENTURY (Heritage, 2021)
The purpose of this paper is to present descriptions of nurses and first female physcians in Serbia. I  used different types of literary genres and applied methods of New Historcism, Literary Theory and Feminist Theories. The authors of these descriptions were women and men of different social status: princess/queen, nurse, actress, physician; police officer and a prison accountant.  The princess Natalie Obrenović and the actress Milka Grgurova described the work of Serbian and Russian nurses  in different places during the Serbo-Turkish War in 1876. Later in her memoir, queen Natalie Obrenović wrote about a big humanitarian role of Belgrade women during the Serbo-Bulgarian War in 1885. The first Serbian police officer and one of the first Serbian female physicians described first female physicians in their diaries while Milutin A. Popović depicted compassionate nurses in the Album of female prisoners. These literary works have been keeping facts about important roles of Martha von Sabinin, a renowned Russian worker who in the past received many Serbian medals, but in the present has remained forgotten. Literature allows completer knowledge and a better understanding about the history of nurses and international bonds, but it also discovers counteractions. For example, Queen Natalie had a leadership role in organizing Belgrade women as nurses during the Serbo-Bulgarian War in 1885. These facts were not mentioned in the  memoirs by a Head of the Army Medical Corps, Vladan Đorđević. While male authors shortly described Serbian female medical doctors and nurses, female authors provided more details in selfdocumenting their role and the role of women from other countries, especially Martha von Sabinin. Some important similarities between diaries by Draga Ljočić and Marie Curie are found and presented. The author of the paper stressed the need of thinking across disciplinary perspectives and borders.
Keywords: women as health professionals, history of nursing, Serbian literature, 19th century, women's life narratives, international humanitarian aid, Martha von Sabinin, Marie Curie